Chronic active EBV infection associated with NK cell lymphoma and hemophagocytic lymphohistiocytosis in a 27-year-old woman: A case report. Issue 2 (January 2019) - Wang, Ya-Dong; Wu, Ling-Ling; Ma, Lu-Yuan; Shang, Xiao-Bo; Li, Zi-Yue; Wang, Wei; Shen, Chuan; Yang, Jing-Jing; Sun, Li-Xia; Zhao, Cai-Yan
Abstract: Rationale: Chronic active Epstein-Barr virus infection (CAEBV) is a common infectious disease that often affects multiple organs or systems. However, it is liable to be neglected and misdiagnosed owing to its insidious onset, lack of specific findings in the early phase, and a general lack of awareness among clinicians. Patient concerns: a 27-year-old woman case has been described who was initially misdiagnosed as drug-induced liver injury due to onset presentation of mild splenomegaly, recurrent liver dysfunction, and disputable pathological evidence of liver biopsy. Diagnoses: CAEBV complicated with natural killer (NK) cell lymphoma and hemophagocytic lymphohistiocytosis (HLH) was diagnosed by in situ hybridization of liver tissue section with EBV-encoded RNA -1 probe and flow cytometry of bone marrow. Interventions: After admission, the patient received symptomatic treatment and antiviral therapy (combination of acyclovir and foscarnet sodium) as well as adjuvant treatment (thymosin alpha 1 and methylprednisolone); later, the patient received etoposide and dexamethasone for diagnosis of EBV associated HLH. Subsequently, the disease progressed to NK cell lymphoma and the patient received the revised EPOCH chemotherapy regimen [etoposide (100 mg/d, d1–5), dexamethasone (7.5 mg/d, d1–5; 5 mg/d, d6–14), cyclophosphamide (0.8 g/d, d1–2), and pegaspargase (3750 u/d, tid, d1–2)]. Outcomes: Although the patient received a series of therapies and other comprehensive measures, finally she died of gastrointestinal hemorrhage and multiple organ failure. Lessons: Liver is one of the main target organs of EBV infection. In the clinical setting of unexplained fever and liver injury, it is necessary to be aware of CAEBV, as well as its fatal complication such as EBV associated NK cell lymphoma and HLH.